2021
DOI: 10.1039/d1tb01061a
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess-inspired synthesis of multilayered chitosan/CaCO3composites with nacre-like structures and high mechanical properties

Abstract: The formation of natural structures found in biological systems is wonderful and fabricates biomaterials at ambient temperatures, in contrast to our artificial technologies wherein harsh conditions are common prerequisites. A...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Moreover, the prominent mountain-like protrusions and depressions on the film's surface promote water capture, leading to the formation of a hydrophilic barrier layer that imparts oil repellency and underwater superoleophobicity. [136] Consequently, these CaCO 3 /organic hybrid films possess dual characteristics of exceptional superhydrophilicity and remarkable underwater superoleophobicity. Based on this intriguing phenomenon, extensive investigations have been conducted to explore their potential applications in oil-water separation.…”
Section: Oil-water Separationmentioning
confidence: 99%
“…Moreover, the prominent mountain-like protrusions and depressions on the film's surface promote water capture, leading to the formation of a hydrophilic barrier layer that imparts oil repellency and underwater superoleophobicity. [136] Consequently, these CaCO 3 /organic hybrid films possess dual characteristics of exceptional superhydrophilicity and remarkable underwater superoleophobicity. Based on this intriguing phenomenon, extensive investigations have been conducted to explore their potential applications in oil-water separation.…”
Section: Oil-water Separationmentioning
confidence: 99%
“…121,165 Li et al (2021) also observed the formation of calcite thin films using a direct mixing method and noted that the films began as disks at sites of high concentration of PAA/carboxyl groups. 173 Contrarily, when CaCO 3 films were formed onto PAA by Wada et al (2004) or Suzuki et al (2016) (both using the ammonium carbonate method), they were comprised of aragonite and vaterite. 168,174 Wada et al (2004) observed CaCO 3 crystallites with a (001) preferred orientation, 174 while Suzuki et al (2016) observed c-axis inhibition.…”
Section: Chitosan As a Substrate For Studies Of Other Macromoleculesmentioning
confidence: 99%
“…The diversity in film morphologies well-illustrates the breadth of PAA results. For example, Kato et al (1998, 2000) used a gas diffusion method and observed the formation of thin film calcite where vertical growth was further suppressed as the concentration of PAA increased. , Li et al (2021) also observed the formation of calcite thin films using a direct mixing method and noted that the films began as disks at sites of high concentration of PAA/carboxyl groups . Contrarily, when CaCO 3 films were formed onto PAA by Wada et al (2004) or Suzuki et al (2016) (both using the ammonium carbonate method), they were comprised of aragonite and vaterite. , Wada et al (2004) observed CaCO 3 crystallites with a (001) preferred orientation, while Suzuki et al (2016) observed c -axis inhibition …”
Section: Previous Studies Of Chitin and Chitosan Influence Upon Caco3...mentioning
confidence: 99%
“…Recently, a microscale additive manufacturing mineralization method was proposed for designing a multi-layered organic-inorganic hierarchical structure. The method involved the deposition of chitosan on a glass substrate using the spin coating followed by rinsing and then deposition of CaCO 3 layer via mineralization using the slow dripping of a solution by a peristaltic pump [225]. A simpler version of spin coating is drop coating, where drops of constituent material dispersed in a liquid are deposited on a smooth, flat subtract.…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%